Deterministic bipolar measurement matrices with flexible sizes from Legendre sequence. Issue 11 (1st May 2016) - Zhang, Guohua; Mathar, Rudolf; Zhou, Quan
Abstract : A deterministic method to construct bipolar measurement matrices for compressed sensing is proposed based on Legendre sequences. The novel matrices have remarkably flexible measurement sizes, relatively low coherence and show empirically good performance compared with Gaussian matrices.